CHATGPT: EVERYTHING TO EVERYONE ALL AT ONCE. - PETRICINI, TIFFANY (ETC: A Review of General Semantics, 2023)
The article presents the discussion on humanity has been thrust into yet another mass psychological experiment. Topics include ChatGPT was already capable of writing quality essays, complex codes that would normally take students hours; and ChatGPT offering so many possibilities for so many people all at once, it is a difficult task keep pace with the rapidly developing changes that have been put into motion.